Dielectric properties of strontium iron holmium niobate ceramics - K. Sanjoom (2018)
Strontium iron holmium niobate (Sr(Fe1-xHox)0.5Nb0.5O3) ceramics were synthesized via a solid-state reaction technique. The undoped ceramic showed an orthorhombic phase, but it transformed to a pseudocubic phase for higher Ho concentrations. A low solubility limit of Ho in SFN caused a formation of second phase for the x=0.15 ceramic. Dielectric behavior of undoped ceramic exhibited high dielectric constant over a wide temperature range. However, the doping shifted this region to a higher temperature. The doping also shifted the peak of dielectric loss to a higher temperature. Activation energy of dielectric relaxation increased with increasing Ho concentration. In addition, complex impedance analysis was applied to determine the behaviors of grain boundary and grain after doping. © 2012 Elsevier Ltd and Techna Group S.r.l.